Anisotropic Magnetic Metamaterial in Numerical Analysis for Electromagnetic-Wave Propagation around Cloaking Device (Global Journal of Science Frontier Research, 2017)
Anisotropic property of media is one function which metamaterials make possible for electromagnetic propagation. Hypothetical magnetic currents in the finite difference time domain (FDTD) method create such anisotropy in permeability in numerical models, in similar way to the modeling of Drude-type permitivity for plasma. Numerical results show clear effects of cloaking in which anisotropic permeability is conceivable by experiments.
Keywords: electromagnetic propagation; Numerical results; anisotropic permeability